Head stabilization in small vertebrates that run at high frequencies with a sprawled posture. (31st March 2020) - Jorissen, Cas; Paillet, Eric; Scholliers, Jan; Aerts, Peter; Goyens, Jana
Abstract: Small animals face a large challenge when running. A stable head is key to maintenance of a stable gaze and a good sense of self-motion and spatial awareness. However, trunk undulations caused by the cyclic limb movements result in involuntary head movements. Hence, the head needs to be stabilized. Humans are capable of stabilizing their head up to 2–3 Hz, but small animals run at cycle frequencies that are up to six times higher. We wondered how natural selection has adapted their head stabilization control. We observed that the relative contributions of vision, on the one hand, and vestibular perception and proprioception, on the other hand, remain the same when lizards undergo fast or slow body undulations in an experimental set-up. Lizards also maintain a short phase lag at both low and high undulation frequencies. Hence, we found no indication that they use a different control mechanism at high frequencies. Instead, head stabilization probably remains possible owing to faster reflex pathways and a lower head inertia. Hence, the intrinsic physical and neurological characteristics of lizards seem to be sufficient to enable head stabilization at high frequencies, obviating the need for evolutionary adaptation of the control pathways. These properties are not unique to lizards and might, therefore, also facilitate head stabilization at high frequencies in other small, fast animals.